APPLIKASI KATA HEAN SANDAN DI DOJO RAUDHATUL JANNAH BATAM - Johan, Mhd.; Evyanto, Winda; Rudianto, Gaguk; Mubarak, Zia Hisni; Oktavia, Yunisa; Afriana, Afriana; Satria, Robby (ASOSIASI IDEBAHASA KEPRI, 2024)
Kata is a significant thing in karate, the aim of this service is to form the young generation of karate and become athletes who excel, especially KATA or karate moves and to form kohai-kohai performances in playing kata, especially kata hean sandan. Kata hean sandan is the third basic kata in karate and is usually played by karateka who hold a yellow to green belt. This kata is also competed in festival and open classes. Apart from that, practicing kata to form the kihon or basic movements of an athlete, when playing this kata you will see the perfect kihon form. Besides that, kata can train and improve a karateka's concentration. The theory used in this analysis is Nakayama's theory, (1979). The method used in this analysis is the direct field survey method. This method will observe the forms of movement carried out by kohai-kohai karate. This method will also act directly and revise movements that are deemed inappropriate. The result of this method is that the kohai's movements immediately change to a better shape.